2011
DOI: 10.2478/v10168-011-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Loudness Assessment of Musical Tones Equalized in A-weighted Level

Abstract: The present study was carried out to determine whether recorded musical tones played at various pitches on a clarinet, a flute, an oboe, and a trumpet are perceived as being equal in loudness when presented to listeners at the same A-weighted level. This psychophysical investigation showed systematic effects of both instrument type and pitch that could be related to spectral properties of the sounds under consideration. Level adjustments that were needed to equalize loudness well exceeded typical values of JND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Notably, the TVL predicted that the mean loudness values for 95% of the amplitude-normalized excerpts were within a range of 4 phons. In comparison, Klonari, Pastiadis, Papadelis, and Papanikolaou (2011) reported that the range of subjective equal loudness judgements on a pair of stimuli corresponding to the same instrument (oboe) sounding the same pitch (A4) reached 3 dB (with the standard presented at 70 dBA), increasing to 5 dB when the pitch varied by as little as a major third. Given that a difference of 1 phon corresponds to a change of 1 dB for a 1000-Hz pure tone (Fastl & Zwicker, 2007), these results suggest that the amplitude-normalized excerpts used in our study were adequately matched for loudness.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the TVL predicted that the mean loudness values for 95% of the amplitude-normalized excerpts were within a range of 4 phons. In comparison, Klonari, Pastiadis, Papadelis, and Papanikolaou (2011) reported that the range of subjective equal loudness judgements on a pair of stimuli corresponding to the same instrument (oboe) sounding the same pitch (A4) reached 3 dB (with the standard presented at 70 dBA), increasing to 5 dB when the pitch varied by as little as a major third. Given that a difference of 1 phon corresponds to a change of 1 dB for a 1000-Hz pure tone (Fastl & Zwicker, 2007), these results suggest that the amplitude-normalized excerpts used in our study were adequately matched for loudness.…”
Section: Discussionmentioning
confidence: 99%
“…frequency parameters (e.g. a desired bandwidth) and amplitude, can be controlled, however as stated by Klonari et al (2011) the problem of loudness estimation and the control of musical sounds has long been an issue in various applications of audio engineering and technology.…”
Section: Methods Proposedmentioning
confidence: 99%
“…The main purpose of SQ metrics is to replace jury tests with an acoustic measurement that would provide an accurate prediction of sound quality judgements made by human listeners. In recent studies several SQ metrics, such as loudness (Fastl, Zwicker, 2007;Klonari et al, 2011), sharpness (Leite et al, 2008;Wang et al, 2007), roughness (Aures, 1985a;Miśkiewicz et al, 2007;Szczepańska-Antosik, 2008; Vencovský, 2016), and tonality (Aures, 1985b;Cuddy et al, 2007;Terhardt et al, 1982) were developed and used for sound quality evaluation (Carletti, 2013; Pleban, 2010). The calculations of individual SQ metrics have been used to compute combined, overall measures of sound quality, such as pleasantness and unbiased annoyance (Kaczmarek, Preis, 2010).…”
Section: Introductionmentioning
confidence: 99%